Pengaruh Media Audio Visual Terhadap Hasil Belajar Siswa pada Materi Pertumbuhan Hewan di Kelas III SD Muhammadiyah 37 Tanjung Selamat - Supiyanti, Supiyanti; Ramadhan, Nuri; Herdyana, Thessa (Tematik: Jurnal Penelitian Pendidikan Dasar, 2024)
This research aims to examine the impact of audio-visual media on student learning outcomes in the subject of animal growth for third-grade students at SD Muhammadiyah 37 Tanjung Selamat. The study employed an experimental method with a "One Group Pretest Posttest Design." The sample consisted of 20 students from the same grade and school. Data collection was conducted through observation and a story-writing test, and the data were analyzed using inferential statistical techniques. The results of the study revealed a significant improvement in student learning outcomes after the use of audio-visual media. Statistical analysis using the t-test showed that the obtained t-value was 4.99 with a degree of freedom (df) of 19 at a significance level of 0.05, with a critical t-value of 1.72. Since t-count > t-table, the null hypothesis (Ho) is rejected and the alternative hypothesis (H1) is accepted. This confirms that the use of audio-visual media significantly improves student learning outcomes in the subject of animal growth for third-grade students at SD Muhammadiyah 37 Tanjung Selamat.